A Contact Lens Patient Referral Form - Passmore, Cedric; Garnett, Brian (Canadian Journal of Optometry, 1981)
You require contact lens information immediately concerning a patient who has come into your office from another city. A simple phone call to the original fitter's office should suffice. That is assuming however, that his receptionist doesn't put you on hold for 10 minutes, and can find the file, or if, when you call, the practitioner is not on holidays, taking a course, out to lunch, or too busy to come to the phone.